2003
DOI: 10.1016/s0006-3495(03)74841-3
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR Studies of Antiamoebin, a Membrane Channel-Forming Polypeptide

Abstract: Antiamoebin I is a membrane-active peptaibol produced by fungi of the species Emericellopsis which is capable of forming ion channels in membranes. Previous structure determinations by x-ray crystallography have shown the molecule is mostly helical, with a deep bend in the center of the polypeptide, and that the backbone structure is independent of the solvent used for crystallization. In this study, the solution structure of antiamoebin was determined by NMR spectroscopy in methanol, a solvent from which one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…The stereospecific assignment for H-atoms in prochiral CH 2 groups and for Me groups of Aib residues was achieved by a combined analysis of vicinal J couplings and intensities of ROESY cross-peaks. The assignments for 1 H-and proton-bearing 13 C-nuclei are in agreement with those reported previously by Galbraith et al [28].…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The stereospecific assignment for H-atoms in prochiral CH 2 groups and for Me groups of Aib residues was achieved by a combined analysis of vicinal J couplings and intensities of ROESY cross-peaks. The assignments for 1 H-and proton-bearing 13 C-nuclei are in agreement with those reported previously by Galbraith et al [28].…”
supporting
confidence: 92%
“…The 13 C constant time HSQC spectrum for the stable isotope-labeled peptide in CD 3 OH solution ( Fig. 1, a) is identical to the HSQC spectrum published by Galbraith et al for Aam-I at natural isotopic abundance [28]. Absence of surplus cross-peaks in this spectrum along with an inspection of the HPLC chromatogram (not shown) indicated purity of the peptide sample.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Since the structure of a peptaibol might be dependent on the environment [7] [8], the Zrv structure was also investigated in various membrane-mimicking solvents (mixtures of CD 3 Cl 3 , CD 3 OH, and H 2 O). The NMR results, however, showed that the conformation appears rather solvent-independent [6] [9].…”
mentioning
confidence: 99%